1979-80 Annual Plan, Planning Department Himachal Pradesh - Planning Commission (Planning Commission, 1979)
The performance of the economy of Himachal Pradesh has been encouraging during the first year of the Five Year Plan 1978-83. It has acquired an unprecedented degree of resilience resulting from attainment of substantial growth rates during 1977-78 and 1978-79 and a fine record of price stability. Growth impulses generated during 1977-78 have been carried forward in 1978-79 and, on the whole, the economy seems well set on the path of development. Although, the rate of growth of the state domestic product has been much lower than in 1977-78, there are emerging trends which indicate a growing strength and buoyant state of economy which can be exploited for further growth. The march of economy realised during 1977-78 has been carried forward despite heavy natural odds against it. the rates of economic growth during 1977-78 and 1978-79 have been 7.9 per cent and 3.5 percent, respectively. This has been made possible only with a large scale realignment of the economic policies by the State Government in favour of poorer sections of our society and redefining the structure of the provision of essential basic facilities.
State Planning Machinery, Planning Department Himachal Pradesh